DEVELOPMENT OF THE CREATIVE ABILITIES OF FUTURE MUSIC TEACHERS THROUGH DIGITAL EDUCATIONAL TECHNOLOGIES - Shaykulov Shukhrat Shodiyevich (Journal of Applied Science and Social Science, 2026)
This article analyzes the role of digital educational technologies in developing the creative abilities of future music teachers. It highlights the application of modern digital tools (MIDI, DAW, virtual instruments, interactive notation software, online platforms, mobile applications) in music education and their role in fostering creative thinking. Additionally, the article examines the factors hindering the use of digital technologies and proposes ways to overcome them.